2021
DOI: 10.1080/1068316x.2021.1909022
|View full text |Cite
|
Sign up to set email alerts
|

Legal cynicism, but not depression, mediates the link between adverse environmental factors and youth’s political violence support

Abstract: Acknowledgements:We would like to thank our 54 test supervisors who helped to conduct study 2 as well as all research assistants and interns involved in data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Family violence included variables such as parental violence and harsh treatment (Baier et al, 2016; Clemmow, 2020; Dhumad et al, 2020; Jahnke et al, 2021; Vukcevic Markovic et al, 2021), violence between parents (Manzoni et al, 2019) and being a perpetrator of domestic abuse (Clemmow, 2020). A meta‐analysis of these studies (see Figure 9) showed that the relation between family violence and radicalization was nonsignificant ( z = 0.052, 95% CI = −0.032, 0.135), with heterogeneous studies ( Q = 39.217, df = 5, p < 0.001, I 2 = 87.250).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Family violence included variables such as parental violence and harsh treatment (Baier et al, 2016; Clemmow, 2020; Dhumad et al, 2020; Jahnke et al, 2021; Vukcevic Markovic et al, 2021), violence between parents (Manzoni et al, 2019) and being a perpetrator of domestic abuse (Clemmow, 2020). A meta‐analysis of these studies (see Figure 9) showed that the relation between family violence and radicalization was nonsignificant ( z = 0.052, 95% CI = −0.032, 0.135), with heterogeneous studies ( Q = 39.217, df = 5, p < 0.001, I 2 = 87.250).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the field can sometimes report multiple and similar variables using the same sample (e.g., discussed politics with mother in relation to radicalization and discussed politics with father in relation to radicalization, European Values Study, 2008), data from the same project can be published in multiple documents (e.g., a doctoral thesis and a journal article, Clemmow, 2020; Clemmow et al, 2020), and data from one project can be reported taking into account different subsamples in the same paper or in different papers (e.g., males and females, Jahnke et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations